2007
DOI: 10.1103/physrevlett.99.027204
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Dominant Precession-Damping Mechanism in Fe, Co, and Ni by First-Principles Calculations

Abstract: The Landau-Lifshitz equation reliably describes magnetization dynamics using a phenomenological treatment of damping. This Letter presents first-principles calculations of the damping parameters for Fe, Co, and Ni that quantitatively agree with existing ferromagnetic resonance measurements. This agreement establishes the dominant damping mechanism for these systems and takes a significant step toward predicting and tailoring the damping constants of new materials.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
334
4
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(369 citation statements)
references
References 30 publications
29
334
4
2
Order By: Relevance
“…A large number of theoretical approaches to the Gilbert damping has been worked out during the last two decades; here we mention only schemes within the oneelectron theory of itinerant magnets, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where the most important effects of electron-electron interaction are captured by means of a local spin-dependent exchangecorrelation (XC) potential. These techniques can be naturally combined with existing first-principles techniques based on the density-functional theory, which leads to parameter-free calculations of the Gilbert damping tensor of pure ferromagnetic metals, their ordered and disordered alloys, diluted magnetic semiconductors, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of theoretical approaches to the Gilbert damping has been worked out during the last two decades; here we mention only schemes within the oneelectron theory of itinerant magnets, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] where the most important effects of electron-electron interaction are captured by means of a local spin-dependent exchangecorrelation (XC) potential. These techniques can be naturally combined with existing first-principles techniques based on the density-functional theory, which leads to parameter-free calculations of the Gilbert damping tensor of pure ferromagnetic metals, their ordered and disordered alloys, diluted magnetic semiconductors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8]15,16 Other routes to the Gilbert damping employ relaxations of occupation numbers of individual Bloch electron states during quasistatic nonequilibrium processes or transition rates between different states induced by the spin-orbit (SO) interaction. [9][10][11][12]14,20 The dissipation of magnetic energy accompanying the slow magnetization dynamics, evaluated within a scattering theory or the Kubo linear response formalism, leads also to explicit expressions for the Gilbert damping tensor. 13,[17][18][19] Most of these formulations yield relations equivalent to the so-called torquecorrelation formula…”
Section: Introductionmentioning
confidence: 99%
“…Ebert et al 1 and Lounis et al 28 suggested that α int is proportional to n(E F ) in the breathing Fermi-surface model (that is, intraband transitions) in the cases of a minimally varying spin-orbit coupling (SOC) (as is the case for the Co x Fe 1−x system) and small electron-phonon coupling 2,29 . Alternatively, interband transitions become significant only if bands have a finite overlap due to band broadening, caused for example by coupling to the phonons.…”
mentioning
confidence: 99%
“…The importance of the nonadiabaticity for current-induced domain wall motion, has led to a number of theoretical [23][24][25][98][99][100][101][102][103][104][105][106] and experimental studies [94,[107][108][109][110][111][112] to determine the nonadiabatic spin torque parameter. Several mechanisms for the nonadiabatic spin transfer torque have been proposed.…”
Section: Non-local Spin Transfer Torque For a Narrow Domain Wallmentioning
confidence: 99%
“…For example, a phenomenological treatment of the scattering of itinerant electrons by spin-dependent impurities generates both damping and a nonadiabatic spin transfer torque in the presence of current [24]. Similarly, band structures with spin-orbit coupling and electron scattering give both damping [113] and nonadiabatic torques [103], both of which can be calculated from first principles [104,105].…”
Section: Non-local Spin Transfer Torque For a Narrow Domain Wallmentioning
confidence: 99%